Awareness of local food handlers towards food hygiene: a study on local food premise in UiTM Dungun and surrounding areas / Nik Nur Halmemi Nik Mohd Halmi & Nurul Izatul Akmal Abdul Rahman - Nik Mohd Halmi, Nik Nur Halmemi; Abdul Rahman, Nurul Izatul Akmal (2016)
The issue of lack of knowledge, attitude and practices among food handlers has become a dominant problem in the foodservice industry. Food safety is one the key public health concern because people eat their meals inside or outside home. The most important strategies to reduce the food borne diseases are by give adequate training to food handlers. Food handlers have a prime role in food businesses, and that is to guarantee that meals served are hygienic for consumption. Conscious or inadvertent contamination of such food places consumers at risk of suffer from foodbome illnesses. For this reason the study was carried out to document the food hygiene knowledge, attitudes and practices of food handlers, in UiTM Dungun and surrounding areas to evaluate the awareness of local food handlers towards hygiene. Food poisoning and other food borne diseases could occur through poor hygiene practices, especially in areas where food and drinks are served. Therefore, there is a need to look into the operations of food vendors to ascertain whether they are followed the proper hygiene practices. The study was descriptive cross- sectional in design with a simple random sampling technique applied in selecting 31 food handlers. Study specific structured questionnaires were used in the data collection. Data were processed into statistical package for social sciences version 23 for analysis. Results indicated that females comprising 51.6% dominated the food handler establishment compared to male 48.4%. Based on the results, among the three elements the majority of the respondents agreed that safe food handling is an important part of job responsibilities with the higher mean score (M=4.58, SD=.5O2) in the attitude in food hygiene. Meanwhile, the lowest mean score amongst the elements also the attitude in food hygiene which majority of them agreed that food handlers should be medically examined every six months with the lowest mean score (M=1.65, SD=.755).